Import Dependence of Exports, Aggregate Demand and Income Distribution in the Turkish Economy: A Post-Keynesian Econometric Analysis - Ozan Ekin Kurt (İzmir İktisat Dergisi)
This study aims to investigate the impact of import dependence on exports on the relation between aggregate demand and functional distribution of income in the Turkish economy. To achieve this, the model proposed by Stockhammer, Hein, and Grafl (2011) was employed and applied to the Turkish economy throughout 1988-2019. The findings indicate that the demand regime was wage-led in Türkiye throughout the sample period, and the integration of import content of exports into the analysis renders the demand regime even slightly more wage-led. Subperiod analyses show that even though the negative effect of a higher labor share in total income on net exports has doubled in absolute value from the 1995-98 subperiod to the 2008-18 subperiod, the positive effect of a higher labor share on private consumption expenditures did not only counterbalance but exceeded it, while its negative effect on private investment remained relatively small and constant over the subperiods. Our findings also show that the integration of import content of exports into the analysis also rendered all the subperiods moderately more wage-led.